Analisis Kebijakan Pengelolaan Hutan Pendidikan: Studi Kasus Hutan Pendidikan Bengo-Bengo Universitas Hasanuddin - Adrayanti Sabar; Yusran Yusran (Fakultas Kehutanan, Universitas Hasanuddin, 2017)
Forest Education as one of forest area with the special purpose for the research and development, education and training and religion and culture. Forest Education Hasanuddin University is used as a vehicle for the community, especially students and researchers to study forests and interrelationships between components of the ecosystem. In the implementation of Forest Education activity does not occur a bit of intersection between stakeholders in the management. This research was conducted in Bengo-Bengo Forest Education, Hasanuddin University, through literature study and secondary data analysis. This study aims to examine policies and regulations related to the management of forest areas with a specific purpose, especially forest education. More specifically, this study aims to (i) identify laws and regulations governing directly or indirectly forest education, from central to local levels, (ii) reviewing policies and regulations, including reviewing the consistency and synchronization of those policies, and (iii) recommend the forest management education policy